2004
DOI: 10.1001/archsurg.139.11.1237
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Limb Perfusion for Unresectable Melanoma of the Extremities

Abstract: In patients with truly unresectable melanoma of the extremities, results after isolated limb perfusion (ILP) are absent in the literature. Complete response rates are probably lower than the reported 54% for locoregional recurrent melanoma. In these patients, ILP with melphalan and tumor necrosis factor ␣ (TNF-␣) could be superior to ILP with melphalan alone. Design: Retrospective analysis with a median follow-up period of 21 months (interquartile range, 9-40 months). Setting: Two tertiary care cancer centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 27 publications
4
29
0
4
Order By: Relevance
“…36 Growth of a those tumors in a heterotypical location on the footpad allows an easy local administration of TNF as well as an assessment of tumor growth by simple measurements, mimicking peripheral tumors in humans which are treated with TNF perfusion. 25,26 In accordance with the results obtained in vitro, we have observed that combination of TNF with bortezomib significantly inhibited tumor growth and prolonged survival of animals bearing the C-26 tumors. Mice bearing LLC tumors responded in a similar way, despite an apparent lack of effects in vitro; however, we were unable to obtain data that were statistically significant due to ample variations in the volume of control tumors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…36 Growth of a those tumors in a heterotypical location on the footpad allows an easy local administration of TNF as well as an assessment of tumor growth by simple measurements, mimicking peripheral tumors in humans which are treated with TNF perfusion. 25,26 In accordance with the results obtained in vitro, we have observed that combination of TNF with bortezomib significantly inhibited tumor growth and prolonged survival of animals bearing the C-26 tumors. Mice bearing LLC tumors responded in a similar way, despite an apparent lack of effects in vitro; however, we were unable to obtain data that were statistically significant due to ample variations in the volume of control tumors.…”
Section: Discussionsupporting
confidence: 86%
“…[17][18][19][20][21][22][23] Several cytokines, including tumor necrosis factor (TNF), have been tested as anticancer agents either alone or in combination with common chemotherapeutics. 24 TNF is used in the clinic for isolated limb perfusion in patients suffering from advanced soft tissue sarcomas and melanomas 25,26 or for isolated perfusion of metastases. 27 Binding of TNF to its type I receptor (TNFR1) results in initiation of the extrinsic apoptotic pathway via caspase-8 cleavage.…”
mentioning
confidence: 99%
“…157,158 Although other agents have been used for ILP, and many have yet to be tested, melphalan (L-phenylalanine mustard) is the cytotoxic agent most commonly used, often in combination with either actinomycin D or TNF-alfa. [158][159][160][161] Response rates after ILP have improved as the method has been refined. A large systematic review (n=2018 ILPs; 22 trials) found that for patients with unresectable stage IIIB-IIIC metastatic melanoma of the limbs, studies published between 1990 and 2008 reported a median overall response rate of 90% (range, 64%-100%) and a median complete response rate of 58% (range, 25%-89%).…”
Section: Regional Therapy: Isolated Limb Perfusion and Infusionmentioning
confidence: 99%
“…1 To date, we have treated more than 150 patients using this novel approach. Based on prior experience with selective IA chemotherapy for the treatment of ocular retinoblastoma, 2 and the high local control rates achieved with selective IA injection of chemotherapy in recurrent limb melanoma, 18 we postulated that SIAC with selective injection of melphalan in the arteries feeding the metastatic disease would be feasible and safe and might prove beneficial in achieving local control of the spinal tumor.…”
Section: Discussionmentioning
confidence: 99%